FORMULATION AND EVALUATION OF TRANSDERMAL PATCHES OF GLIZPIZIDE - YASH PAUL; HIMANSHI TANWAR (International Journal of Pharma and Bio Sciences, 2014)
Drug Delivery through skin would provide a useful alternative to oral delivery, which has numerous side effects. Therefore, the present investigation was aimed to develop sustained release transdermal therapeutics system containing Glipizide with varying ratios of HPMC & PVPK30 using solvent evaporation technique. Ten different formulations were prepared keeping the concentration of Glipizide constant as 45mg in each formulation. The films were developed and evaluated for thickness, weight variation, percent moisture absorption, percent moisture loss, folding endurance, drug content and in vitro drug dissolution studies. Finally, on the basis of best release one of the formulations was selected for further kinetic studies which exhibited that release rate followed Fickian’s diffusion law. The selected formulation showed no sign of irritation when studied using mice skin. Finally, it was concluded that Glipizide transdermal patch could improve the bioavailability of the drug by avoiding its first pass metabolism